TiCaPCON-Supported Pt- and Fe-Based Nanoparticles and Related Antibacterial Activity - Ponomarev, Viktor A; Sheveyko, Aleksander N; Permyakova, Elizaveta S; Lee, Jihyung; Voevodin, Andrey A; Berman, Diana; Manakhov, Anton M; Michlíček, Miroslav; Slukin, Pavel V; Firstova, Viktoriya V; Ignatov, Sergey G; Chepkasov, Ilya V; et al. (ACS applied materials & interfaces, 2019)
A rapid increase in the number of antibiotic-resistant bacteria urgently requires the development of new more effective yet safe materials to fight infection. Herein, we uncovered the contribution of different metal nanoparticles (NPs) (Pt, Fe, and their combination) homogeneously distributed over the surface of nanostructured TiCaPCON films in the total antibacterial activity toward eight types of clinically isolated bacterial strains (Escherichia coli K261, Klebsiella pneumoniae B1079k/17-3, Acinetobacter baumannii B1280A/17, Staphylococcus aureus no. 839, Staphylococcus epidermidis i5189-1, Enterococcus faecium Ya-235: VanA, E. faecium I-237: VanA, and E. coli U20) taking into account various factors that can affect bacterial mechanisms: surface chemistry and phase composition, wettability, ion release, generation of reactive oxygen species (ROS), potential difference and polarity change between NPs and the surrounding matrix, formation of microgalvanic couples on the sample surfaces, and contribution of a passive oxide layer, formed on the surface of films, to general kinetics of the NP dissolution. The results indicated that metal ion implantation and subsequent annealing significantly changed the chemistry of the TiCaPCON film surface. This, in turn, greatly affected the shedding of ions, ROS formation, potential difference between film components, and antibacterial activity. The presence of NPs was critical for ROS generation under UV or daylight irradiation. By eliminating the potential contribution of ions and ROS, we have shown that bacteria can be killed using direct microgalvanic interactions. The possibility of charge redistribution at the interfaces between Pt NPs and TiO2 (anatase and rutile), TiC, TiN, and TiCN components was demonstrated using density functional theory calculations. The TiCaPCON-supported Pt and Fe NPs were not toxic for lymphocytes and had no effect on the ability of lymphocytes to activate in response to a mitogen. This study provides new insights into understanding and designing of antibacterial yet biologically safe surfaces.
Keywords: antibacterial films; electrochemical behavior; testování materiálů; Materials Testing; železo; antibakteriální látky; platina; Bacteria; Platinum; lymfocyty; bactericide ion release; kovové nanočástice; Metal Nanoparticles; lidé; Anti-Bacterial Agents; Iron; Humans; Lymphocytes; reactive oxygen species; Kelvin probe force microscopy; microgalvanic effect